Pentahelix Model in Planning Sport Tourism and Events in Hambalang Village, Bogor Regency - Arinil Haq, Elga Hening; Mbulu, Yustisia Pasfatima; Rossi, Fetty Nurmala (E-Journal of Tourism, 2023)
This study aims to analyze sports tourism and tourism sport in Hambalang Village, analyze sport event planning in Hambalang Village and create a Pentahelix model for planning sports tourism and events in Hambalang Village. This study uses a descriptive qualitative approach with an analysis of the event management cycle Goldblatt. This research data collection method was obtained through observation and interviews with five stakeholders (academics, business, community, government and media). Based on the results of this study shows that sports tourism and tourism sports in Hambalang Village have developed quite rapidly. Hambalang Village, which has good geographical characteristics, namely its location on high land, has good natural and sport potential, being an alternative for recreational sports for some sports lovers. In the event planning that has been carried out, Hambalang Village has carried out event planning in a structural manner and by the three stages of event management, namely research design and planning. While the pentahelix model in planning sports tourism and events in Hambalang Village is currently running well, the collaboration is carried out by the functions and parts of each stakeholder: academia, business, community, government, and media, synergize in tourism development. So the results of the analysis of sport and tourism and the study of the event management cycle can produce a pentahelix model for planning sports tourism and events in Hambalang village.